Enhancing e-accounting adoption: An analysis of the influence of relative advantage, management support and information system quality on organization - Hidayati, Irma; Djatmika, Ery Tri; Wardoyo, Cipto; Restuningdiah, Nurika (Edelweiss Applied Science and Technology, 2025)
This study examines the key factors influencing e-accounting adoption among MSMEs in Malang City, focusing on its role in enhancing operational efficiency and financial transparency. The research explores the impact of six variables—Relative Advantage, Management Support, Competitive Pressure, System Quality, Information Quality, and Service Quality—on adopting e-accounting. Using Partial Least Squares - Structural Equation Modeling (PLS-SEM), the study identifies that Relative Advantage, System Quality, and Service Quality significantly influence adoption. However, their relationships are negatively directed, indicating a gap between user expectations and actual experiences. Conversely, Management Support, Competitive Pressure, and Information Quality do not show significant effects. The study concludes that improving system and service quality, alongside targeted education and training, is crucial for MSMEs to fully benefit from e-accounting. Practical implications suggest strategies for technology providers, policymakers, and MSMEs to optimize e-accounting for better business efficiency and sustainability.